2022
DOI: 10.1101/2022.06.06.494981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PLK4 drives centriole amplification and apical surface area expansion in multiciliated cells

Abstract: Multiciliated cells (MCCs) are terminally differentiated epithelia that assemble multiple motile cilia used to promote fluid flow. To template these cilia, MCCs dramatically expand their centriole content during a process known as centriole amplification. In cycling cells, the master regulator of centriole assembly Polo-like kinase 4 (PLK4) is essential for centriole duplication; however recent work has questioned the role of PLK4 in centriole assembly in MCCs. To address this discrepancy, we created genetical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…proved that proteins that control cell cycle progression are also essential to drive multiciliated cell differentiation (Al Jord et al, 2017). Very recently, it was suggested that PLK4 protein and its kinase activity are essential for centriole amplification in multiciliated cells (LoMastro et al, 2022). These results corroborate the idea that the initial stages of centriole assembly are conserved between cycling and multiciliated cells.…”
Section: Discussionmentioning
confidence: 99%
“…proved that proteins that control cell cycle progression are also essential to drive multiciliated cell differentiation (Al Jord et al, 2017). Very recently, it was suggested that PLK4 protein and its kinase activity are essential for centriole amplification in multiciliated cells (LoMastro et al, 2022). These results corroborate the idea that the initial stages of centriole assembly are conserved between cycling and multiciliated cells.…”
Section: Discussionmentioning
confidence: 99%